BRCA1 and BRCA2 Large Genomic Rearrangements Screening in Thai Familial Breast Cancer Patients by Multiplex Ligation-dependent Probe Amplification (MLPA) - Jadsri, Sunichya; Chareonsirisuthigul, Takol; Rerkamnuaychoke, Budsaba; Dejsuphong, Donniphat; Tunteeratum, Atchara; Mahasirimongkol, Surakameth (Naresuan University Journal: Science and Technology (NUJST); Vol 24 No 2 (2016): May-August 2016, 2016)
Breast Cancer has now become the most frequently diagnosed cancer and the leading cause of cancer death in females. BRCA1 and BRCA2 inherited mutations account for 5%-10% of all female breast cancers. However, prevalence of BRCA genes mutation is vary in between difference populations. In Thailand, there are no previous studies of BRCA1 and BRCA2 large genomics rearrangement (LGRs) have been reported. In this study, we screened the ‘‘high-risk’’ group consisted of 100 individuals who met clinical criteria for genetic examination of BRCA1/2 using Multiplex Ligation-dependent Probe Amplification (MLPA). Among a total of 100 selected cases, one duplication of BRCA1 exon 15 was determined but none of any LGRs were found in BRCA2. Similar to the other studies in Asian population, the prevalence of LGRs in Thailand likely to be low. The information of BRCA1 and BRCA2 LGRs from this study can be used as a nationwide of Thai database which will be useful for further study of the familial breast cancer. Keywords : Breast Cancer, BRCA1/2 Mutation, Multiplex Ligation-dependent Probe Amplification (MLPA)
Keywords: Breast Cancer, BRCA1/2 Mutation, Multiplex Ligation-dependent Probe Amplification (MLPA)